The Influence Factors of Continuance Intention to Use a Music Streaming Application - Diyah Wulandari; Usep Suhud; Unggul Purwohedi (International Journal on Advanced Science, Education, and Religion, 2019)
Currently, streaming music applications have a high demand by smartphone users in Indonesia. Streaming music applications is new trend and can’t be separated from the people daily life, because of the need for full access, easy and inexpensive music services. This study aimed to find out the factors that influence continuance intention to use a music streaming application. This study uses variable perceived ease of use, perceived enjoyment, entertainment, habit, social influence, satisfaction and continuance intention. The data used in research is primary data obtained from online questionnaires. Sample in this study were 200 respondents streaming music application users from Spotify in the Greater Jakarta area. The sampling technique of this study was non-probability sampling with purposive sampling method. This study uses a quantitative approach through statistical analysis. Tests conducted using Structural Equation Modeling (SEM) with the help of analysis of moment structures (AMOS 24). This result shows that perceived ease of use, perceived enjoyment, and entertainment have a positive and significant effect toward satisfaction. Satisfaction and habit have a positive and significant effect toward continuance intention. Meanwhile social influence has a negative and significant effect toward continuance intention.